Translation and psychometric properties of the Persian version of the position on nursing diagnosis scale - Tayebeh Ramezanian; Fatemeh Mohammadipour; Rasool Mohammadi; Parastou Kordestani‐Moghaddam (Wiley, 2021)
Abstract Aim To validate the Positions on Nursing Diagnosis scale developed by Lunney and Krenz (1992) in Persian language. Design Cross‐sectional survey. Methods A methodological study conducted in two stages of translation (by applying the forward and back‐translation method) and psychometric assessment was conducted in a western area of Iran. The scale was completed by 600 nurses selected by quota method from different wards of four provinces. Date of data collection is 1‐April‐2019 to 1‐Dec‐2019. Results The Positions on Nursing Diagnosis scale showed acceptable content validity with index of 0.97. The 20 items of the Positions on Nursing Diagnosis scale load on four factors. The confirmatory factor analysis demonstrated the good fit of the model's indicators. Cronbach's alpha coefficient for the whole instrument was 0.85. The intraclass correlation coefficient was 0.86.